The Influence of Brand Image and Product Quality on Purchasing Decisions for Avoskin Skincare Products Mediated by Consumer Trust in Ternate City - Mutia Abd. Gani, Siti; Mohungo, Yolanda; Sarju, Himawan (IJBLE Scientific Publications Community Inc., 2026)
This study aims to analyze the effects of brand image and product quality on the purchasing decisions of Avoskin skincare products, with consumer trust as the mediating variable. This research employs a quantitative, survey-based approach. The sample consists of 126 respondents who are consumers of Avoskin skincare products in Ternate City, selected using purposive sampling. Data were collected through questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that brand image and product quality have a positive and significant effect on purchasing decisions. Brand image and product quality also have a positive and significant effect on consumer trust. Consumer trust has a positive and significant effect on purchasing decisions. Furthermore, consumer trust does not mediate the effect of brand image on purchasing decisions but partially mediates the effect of product quality on purchasing decisions.